Neuropeptide‐Y levels in ST‐segment–elevation myocardial infarction: relationship with coronary microvascular function, heart failure, and mortality - Gibbs, T; Tapoulal, N; Shanmuganathan, M; Burrage, MK; Borlotti, A; Banning, AP; Choudhury, RP; Neubauer, S; Kharbanda, RK; Ferreira, VM; Channon, KM; Herring, N (American Heart Association, 2022)
Background The sympathetic cotransmitter, neuropeptide Y (NPY), is released into the coronary sinus during ST‐segment–elevation myocardial infarction and can constrict the coronary microvasculature. We sought to establish whether peripheral venous (PV) NPY levels, which are easy to obtain and measure, are associated with microvascular obstruction, myocardial recovery, and prognosis. Methods and Results NPY levels were measured immediately after primary percutaneous coronary intervention and compared with angiographic and cardiovascular magnetic resonance indexes of microvascular function. Patients were prospectively followed up for 6.4 (interquartile range, 4.1–8.0) years. PV (n=163) and coronary sinus (n=68) NPY levels were significantly correlated (r=0.92; P<0.001) and associated with multiple coronary and imaging parameters of microvascular function and infarct size (such as coronary flow reserve, acute myocardial edema, left ventricular ejection fraction, and late gadolinium enhancement 6 months later). We therefore assessed the prognostic value of PV NPY during follow‐up, where 34 patients (20.7%) developed heart failure or died. Kaplan‐Meier survival analysis demonstrated that high PV NPY levels (>21.4 pg/mL by binary recursive partitioning) were associated with increased incidence of heart failure and mortality (hazard ratio, 3.49 [95% CI, 1.65–7.4]; P<0.001). This relationship was maintained after adjustment for age, cardiovascular risk factors, and previous myocardial infarction. Conclusions Both PV and coronary sinus NPY levels correlate with microvascular function and infarct size after ST‐segment–elevation myocardial infarction. PV NPY levels are associated with the subsequent development of heart failure or mortality and may therefore be a useful prognostic marker. Further research is required to validate these findings.